2004
DOI: 10.2139/ssrn.471842
|View full text |Cite
|
Sign up to set email alerts
|

The Reputational Penalty for Aggressive Accounting: Earnings Restatements and Management Turnover

Abstract: ABSTRACT:In this paper we investigate the reputational penalties to managers of firms announcing earnings restatements. More specifically, we examine management turnover and the subsequent employment of displaced managers at firms announcing earnings restatements during 1997 or 1998. In contrast to prior research (Beneish 1999; Agrawal et al. 1999), which does not find increased turnover following GAAP violations or revelation of corporate fraud, we find that 60 percent of restating firms experience a turnove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 45 publications
6
102
0
4
Order By: Relevance
“…Further, our results show there was a significant and positive response by the stock market to CEO certification for firms where the CEO came in after his/her company's financial restatement. This result provides evidence to support the key assumption implicit in prior studies (e.g., ArthaudDay et al, 2006;Desai et al, 2006), that a change in the firm's CEO after the firm has had a financial restatement can help restore investor confidence in the firm's financial statements. Overall, our results suggest that the stock market's assessment of CEO certification credibility (or the CEO's general reputation) is closely linked to whether or not the CEO is associated with the firm's prior restatement, if any.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Further, our results show there was a significant and positive response by the stock market to CEO certification for firms where the CEO came in after his/her company's financial restatement. This result provides evidence to support the key assumption implicit in prior studies (e.g., ArthaudDay et al, 2006;Desai et al, 2006), that a change in the firm's CEO after the firm has had a financial restatement can help restore investor confidence in the firm's financial statements. Overall, our results suggest that the stock market's assessment of CEO certification credibility (or the CEO's general reputation) is closely linked to whether or not the CEO is associated with the firm's prior restatement, if any.…”
Section: Discussionsupporting
confidence: 81%
“…As Arthaud-Day et al argued, 'The executives in office at the time of a restatement are inextricably linked to the restatement by virtue of their physical proximity, temporal connection, and positional authority. This linkage results in their being stigmatized, or discredited, by association with the restatement event' (Arthaud-Day et al, 2006: 1122 Further, as previous studies (e.g., Arthaud-Day et al, 2006;Desai et al, 2006) have shown, a firm often replaces its CEO after a financial restatement. The turnover of the CEO is often used to signal a firm's commitment to change.…”
Section: Ceo and Prior Financial Restatementmentioning
confidence: 99%
See 1 more Smart Citation
“…Early research by Beneish (1999) and Agrawal, Jaffe, and Karpoff (1999) generally failed to find an increase in turnover frequency following accounting irregularities, specifically GAAP violations and the revelation of corporate fraud, respectively. In a more recent study, Desai, Hogan, and Wilkins (2006) examine the frequency of managerial turnover following accounting restatements. They find that 60% of the firms in their restatement sample experienced turnover of at least one top manager within the 24 months following the restatement, compared with 35% among their year-size-industry-matched counterparts.…”
Section: The Role Of Management Incentives In Facilitating the Informmentioning
confidence: 99%
“…Finally, Kedia and Philippon (2006) find that restatements are preceded by a period of excessive investment, employee hiring, and managerial exercise of options, and are followed by sharp disinvestments and employee firing. Desai et al (2006) add that restatements lead to managerial turnover. Palmrose and Scholz (2004) examine the association of restatements with the filing of class action lawsuits, and report that the probability of a lawsuit increases for restatements that involve core earnings, impact a large number of financial accounts, or are the result of fraud.…”
mentioning
confidence: 99%